2018
DOI: 10.3390/molecules23112919
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Derivatives’ Inhibition of Glycogen Synthase Kinase-3β Is the Pharmacological Basis of Kangen-Karyu in Alzheimer’s Disease

Abstract: Inhibition of glycogen synthase kinase 3β (GSK-3β) is considered to be the central therapeutic approach against Alzheimer’s disease (AD). In the present study, boiled water extracts of the Kangen-karyu (KK) herbal mixture and its constituents were screened for GSK-3β inhibitory activity. KK is used in traditional Kampo and Chinese medicines for improving cognitive function. The GSK-3β inhibition potential was evaluated by using the Kinase-Glo luminescent kinase assay platform. Furthermore, enzyme kinetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…not only involved in the regulation of glycogen metabolism, but also play central roles in a variety of signaling pathways which are closely associated with cell mobility, proliferation, and survival [31]. More interestingly, a previous study strongly suggested that GSK3 was responsible for phosphorylating H1.5 at threonine 10 [17].…”
Section: Discussionmentioning
confidence: 99%
“…not only involved in the regulation of glycogen metabolism, but also play central roles in a variety of signaling pathways which are closely associated with cell mobility, proliferation, and survival [31]. More interestingly, a previous study strongly suggested that GSK3 was responsible for phosphorylating H1.5 at threonine 10 [17].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yu et al demonstrated that treatment with S. miltiorrhiza extract at doses of 0.01, 0.1, 0.2 mg/mL for 2 h inhibited ROS generation in SH-SY5Y cells [ 92 ]. In addition, Paudel et al reported on the inhibitory effect of S. miltiorrhiza extract on GSK-3β [ 93 ], while Ozarowski et al examined the inhibitory effect of S. miltiorrhiza extract administration at a dose of 200 mg/kg for 28 days on AChE as well as BuChE and BACE1 in the rat brain cortex [ 94 ]. These multi-functional properties of S. miltiorrhiza extract suggest that it could act on multiple targets for the treatment of cognitive impairment and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…S. miltiorrhiza extract decreased the intracellular reactive oxygen species (ROS) levels, cleaved caspase-3 and cytosolic cytochrome c expression, and Bax/Bcl-2 ratio. Paudel et al reported that S. miltiorrhiza extract significantly inhibited the expression of glycogen synthase kinase-3β (GSK-3β) with IC 50 values of 7.77±1.38 [ 93 ]. According to Ozarowski et al, subchronic (28-fold) oral administration of 200 mg/kg S. miltiorrhiza extract for 28 days led to an improvement in long-term memory of rats as assessed by passive avoidance test, partially through inhibition of acetylcholinesterase (AChE) activity [ 94 ].…”
Section: Nervous System Diseasesmentioning
confidence: 99%
“…In our previous study conducted to evaluate anti-AD activity in vitro via the GSK3 enzyme, boiled water extract of Kangen-karyu demonstrated potent inhibition of GSK3β with an IC 50 value of 17.05 ± 1.14 μg/mL, as shown in Table 4 (39). Also, water extracts of all individual components showed good inhibition with IC 50 values ranging from 7.77 to 93.61 μg/mL.…”
Section: Gsk3β As a Molecular Target Of Kangen-karyumentioning
confidence: 90%